Vitamin D Potentiates the Inhibitory Effect of MicroRNA-130a in Hepatitis C Virus Replication Independent of Type I Interferon Signaling Pathway - Xiaoqiong Duan; Yujuan Guan; Yujia Li; Shan Chen; Shilin Li; Limin Chen (Mediators of Inflammation)
Calcitriol, the bioactive metabolite of vitamin D, was reported to inhibit HCV production in a synergistic fashion with interferon, a treatment in vitro. Our previous study established that miR-130a inhibits HCV replication by restoring the host innate immune response. We aimed to determine whether there is additive inhibitory effect of calcitriol and miR-130a on HCV replication. Here we showed that calcitriol potentiates the anti-HCV effect of miR-130a in both Con1b replicon and J6/JFH1 culture systems. Intriguingly, this potentiating effect of calcitriol on miR-130a was not through upregulating the expression of cellular miR-130a or through increasing the miR-130a-mediated IFNα/β production. All these findings may contribute to the development of novel anti-HCV therapeutic strategies although the antiviral mechanism needs to be further investigated.